Perkawinan, di Bawah Umur Sosialisasi dan Pendampingan Faktor Penyebab dan Dampak Perkawinan di Bawah Umur serta Undang-Undang nomor 16 Tahun 2019 tentang Batas Usia Perkawinan: Sosialisasi dan Pendampingan Perkawinan di Bawah Umur - Sofia Gussevi; Ira Novianty; Melly Agustina; Rifqi Khuzayri; Melly Agustina Melly; Rifqi Khuzayri Rifqi (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
This service activity is motivated by the results of the author's research in 2021 entitled "The Phenomenon of Child Marriage during the Covid-19 Pandemic", there are many underage marriages in 2020. This can be seen from the application for Dispensation for Marriage which was submitted to the Purwakarta Religious Court in 2020 namely as many as 258 cases, while in 2019 only 72 cases. In Law Number 1 of 1974 concerning Marriage, paragraph (1) reveals that the minimum age for marriage is 19 years for men and 16 years for women. Then this minimum age limit was changed with the issuance of Law Number 16 of 2019 which states that the minimum age for marriage is the same as 19 years for men and for women. Although the age of marriage has been set, in reality there are still many cases of child marriage or underage marriage. Based on this, this activity aims to implement the results of the research that has been carried out, using the extension method. The results of this activity show that many people do not know the minimum age to be able to get married as stated in Law Number 16 of 2019. In addition, parents do not provide supervision over their children's association, so that underage marriages occur. many because of Married By Accident (MBA) or pregnant before marriage, or other terms Unwanted Pregnancy (KTD). By holding this service, the community is expected to be able to know and understand the causes and effects of underage marriage and Law Number 16 of 2019 concerning the Age Limit for Marriage.